Ethical Standards in the Process of Counteracting Financial Abuse with Regard to EU Budget Funds. The Case of Poland - Walenia, Alina (Annales. Etyka w Życiu Gospodarczym, 2018)
In accordance with the binding regulations of the EU law, each institution participating in the EU funds management process has in place relevant procedures preventing fraud and corruption and discouraging people from taking such actions. Managing institutions that work in cooperation with organisations which participate in the implementation of EU funds ensures the operation of an effective fraud risk management system and the implementation of effective anti‑fraud means which are designed to protect the financial interests of the European Union. The ethical norms and principles implemented in institutions which coordinate the process of EU funds management are of great importance for the process of reducing fraud related to EU funds. It was confirmed with the results of research carried out that clearly defined standards of employee conduct and determining procedures in the management and control system were the most important factors mitigating the irregularities. A special place was reserved for complying with the norms of ethical conduct and honesty by the employees of institutions managing the EU funds and development of a Code of Ethics which describes the conduct of the employees of institutions participating in the EU funds management process. The anti‑fraud procedures presented herein stem from EU law and are applicable in Poland.